The use of dynamic modeling methods to create an adaptive training system for specialists that meets modern demands in the information field - A. M. Konakov; I. I. Livshits (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the research is to analyze the functionality and features of dynamic modeling as part of training specialists in the field of information security and countering various threats in the information space, taking into account the time factor.Method. The analysis of modeling the basic scenario of incidents and threats to information security, which are the initial data for the formation of the necessary level and requirements for the training of information security specialists, is carried out.Result. A new approach to training specialists in the field of information security has been developed and proposed, taking into account modern needs and requirements. The proposed approach introduces a numerical coefficient that allows us to determine the area of necessary skills and knowledge to prevent and minimize possible incidents over a period of time.Conclusion. The area of information security under consideration, namely the training of qualified specialists with the necessary level of knowledge and skills, is relevant from the point of view of the development of the information technology sector and ensuring the protection of all processes occurring in it. This area requires further attention and the introduction of new approaches and methods of training due to the development of the information society and the need for highly qualified personnel.